2009
DOI: 10.1017/s0030605309990147
|View full text |Cite
|
Sign up to set email alerts
|

Status and distribution of the Endangered banteng Bos javanicus birmanicus in Vietnam: a conservation tragedy

Abstract: From January 2005 to December 2007 field surveys were conducted in the Central Highlands region of Vietnam to assess the status of banteng Bos javanicus birmanicus. The population of banteng was estimated to be 74-103. It has declined by at least 50% since the mid-1990s and the species is likely to go extinct in Vietnam in the near future. Remaining herds are small, although recruitment still exists. Large portions of the species' range in the early 1990s are no longer occupied and the maximum area of occupanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…They feed on a wide variety of plant material, opting to graze in open areas and are more frequently found in open dipterocarp forests when available [15][16][17]. The Bornean subspecies is recorded as living in secondary forests and that logging, which opens up the forest floor, may benefit banteng due to the increased understory growth [14,17,18]. This suggestion is supported by Meijaard and Sheil [19] who observed that, with the exception of frugivores, ungulates are more successful in logged forests.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…They feed on a wide variety of plant material, opting to graze in open areas and are more frequently found in open dipterocarp forests when available [15][16][17]. The Bornean subspecies is recorded as living in secondary forests and that logging, which opens up the forest floor, may benefit banteng due to the increased understory growth [14,17,18]. This suggestion is supported by Meijaard and Sheil [19] who observed that, with the exception of frugivores, ungulates are more successful in logged forests.…”
Section: Introductionsupporting
confidence: 65%
“…Banteng are crepuscular in their activities, spending more time on foraging and social activity at dawn and dusk, while the mid-part of the day is largely spent ruminating (P. Gardner unpublished observations cited in [15]). They feed on a wide variety of plant material, opting to graze in open areas and are more frequently found in open dipterocarp forests when available [15][16][17]. The Bornean subspecies is recorded as living in secondary forests and that logging, which opens up the forest floor, may benefit banteng due to the increased understory growth [14,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…p < 0.1; *p < 0.05 number of identified banteng had a larger herd size range and average, therefore, a declining population likely causes smaller herd sizes, as observed in a population of Bos javanicus birmanicus in Vietnam (Nguyen 2009). Low population densities and restrictions to home range are causing reductions, and subsequent ly extinctions, in other banteng populations (Pedrono et al 2009). This is likely occurring with the Bornean banteng.…”
Section: Herd Demographymentioning
confidence: 99%
“…Internal abandoned logging roads also provide banteng forage due to the increased regeneration of pioneer species over time (Gardner 2015). Moreover, logging roads provide easy access to the previously cultivated areas that provide secondary growth which banteng benefit from (Pedrono et al 2009). Thus, more individuals will be attracted to the available forage, causing larger herds to be vulnerable to human conflict on logging roads.…”
Section: Banteng Herd Sizesmentioning
confidence: 99%
“…The herbivorous bovid, the banteng (Bos javanicus), can be sympatric with R. sondaicus and could have been a potential competitor (Hoogerwerf 1970;Rinaldi et al 1997). Today, the banteng is vulnerable or endangered throughout its remaining range Manh 2009;Pedrono et al 2009;Pudyatmoko et al 2007;Timmins et al 2008), and, typical of the genus Bos, it prefers a grass-dominated diet and drier open habitats under ideal conditions (Hoogerwerf 1970;Steinmetz 2004). Currently, the banteng population in Ujung Kulon National Park is estimated at 200-800 individuals (Alikodra 1987; Ashby and Santiapillai 1988;Timmins et al 2008;World Conservation Monitoring Centre 2005), and ongoing concern over its effects on R. sondaicus has been expressed (Rinaldi et al 1997), although it was not considered a serious potential competitor by Ammann (1985).…”
Section: Ecologymentioning
confidence: 99%